Investigation of floating catalyst CVD for development of CNT-coated carbon fibre reinforced composite - Ismail, Siti Norazian (2010)
Composites produced from untreated carbon fibres result in poor mechanical properties. To increase the bonding between the carbon fibres and the matrix, the surface of the carbon fibres has been coated by carbon nanotubes (CNTs) through CNT-coated carbon fibre treatment process using a floating catalyst chemical vapour deposition (FCCVD) technique. This treatment was carried out with the presence of ferrocene and benzene as the catalyst and carbon precursor. By varying the technique of floating catalyst used to introduce ferrocene into the CVD furnace, it will influence the growth of CNT on the carbon fibre surface and hence influence the strength of the resulting carbon fibre composite. In the present investigation, two types of floating catalyst techniques were explored with different approaches in the way in which the ferrocene was introduced inside the furnace. Each technique was applied by varying two selected parameters which were the reaction temperature and the amount of ferrocene concentration. The reaction temperature was fixed at 700 and 800oC meanwhile the amount of ferrocene was varied between 0.2, 0.5 and 1.0g. Technique 1 was to introduce the vapourized ferrocene and benzene into the furnace by the hydrogen as the carrier gas. Through this, only less CNTs were grown with the presence of carbonaceous products. Meanwhile, in technique 2, the ferrocene was dissolved in liquid benzene before the mist of solution being introduced from outside of the furnace using hydrogen gas. The densely packed pure CNT grown by technique 2 was totally covered the structures of the carbon fibres. This directly affected the increase in surface area of the carbon fibre itself which gave an indication of good adhesion between the carbon fibre and the polypropylene (PP) matrix during the fabrication of composite. The morphology of the carbon fibres after the treatment was analysed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) before being incorporated into the composites. Meanwhile, the energy diffraction x-ray (EDX) characterisation was used to analyze the chemical composition on CNT grown by both techniques. Tensile tests were performed to evaluate the effectiveness of both techniques on the mechanical properties of the composites. The tensile strength and modulus from technique 2 improved by 64% and 109% respectively, compared to the composite made using the untreated carbon fibres. These values were two times higher than tensile properties obtained through composites made from CNT-coated carbon fibre synthesized using technique 1 which recorded 33 and 44% increment in tensile strength and modulus properties.